1‐Methylcyclopropene (1‐MCP)‐Induced Alteration in Leaf Photosynthetic Rate, Chlorophyll Fluorescence, Respiration and Membrane Damage in Rice (Oryza sativa L.) Under High Night Temperature. (11th September 2014) - Mohammed, A. R.; Cothren, J. T.; Chen, M.‐H.; Tarpley, L.
Abstract High night temperature (HNT) can induce ethylene‐triggered reactive oxygen species production, which can cause premature leaf senescence and membrane damage, thereby affecting production, consumption and transfer of photosyn‐thates, and yield. The 1‐methylcyclopropene (1‐MCP) can competitively bind with ethylene receptors and decrease ethylene effects. The objective was to determine the effects of HNT and 1‐MCP on leaf photosynthetic rate (PN), chlorophyll fluorescence, total chlorophyll (TC), respiration, membrane damage, pollen germination, spikelet fertility (SF) and yield of rice hybrid 'XL723'. Plants were grown under ambient night temperature (ANT) (25 °C) or HNT (30 °C) with or without 1‐MCP treatment. Application of 1‐MCP was at the boot stage. The decrease in yield (11 %) under HNT was associated with decreased PN (4 %), stomatal conductance (8 %), quantum yield (11 %) TC (23 %) and SF (5 %) and increased respiration (74 %), Fo/Fm (increase in thylakoid membrane damage; 11 %) and membrane damage (leaf electrolytic leakage; 57 %). The 1‐MCP‐treated plants grown under HNT showed increased yield (17 %), which was associated with increased PN (10 %), stomatal conductance (30 %), quantum yield (9 %), TC (37 %) and SF (11 %) and decreased respiration (39 %), Fo/Fm (5 %) and membrane damage (18 %). Plants grown under HNT showed increased grain chalkiness (154 %) compared with plants grown under ANT.